Kapitał ludzki źródłem elastyczności współczesnych organizacji: Human capital as a source being the flexibility of modern organizations - Bombiak, Edyta (Management and Administration Journal, 2021)
Modern organizations operate in dynamic conditions and more importantly difficult to predict changes in the environment. The ability to quickly adapt to them is determined by the flexibility of operation. The source of this flexibility are versatile and competent staff. Therefore, the growing importance of flexible human capital management recognizes and appreciates more and more companies, regardless of size or form of ownership. The purpose of this article is to discuss the nature and importance of flexibility in the management of employees in the economy based on knowledge and practical ways to implement this concept.